Onde está o pênis? (Revista da Universidade Federal de Minas Gerais, 2012)
While female nudity is widespread in Brazilian society, the male penis representations are still a subject of taboo and secrecy. Drawing back on Brazilian psychoanalyst Angelo Gaiarsa’s criticism on male sexuality, this paper scrutinizes the burden of the symbolic absence of the penis in a set of daily situations, ranging from a documentary film on the lifestyle of the Kamaiura tribe held by Globo TV network, to a workshop on body language and perception.